2020
DOI: 10.3390/md18080423
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Marine Carotenoids: Application by Using Nanoformulations

Abstract: Carotenoids are natural fat-soluble pigments synthesized by plants, algae, fungi and microorganisms. They are responsible for the coloration of different photosynthetic organisms. Although they play a role in photosynthesis, they are also present in non-photosynthetic plant tissues, fungi, and bacteria. These metabolites have mainly been used in food, cosmetics, and the pharmaceutical industry. In addition to their utilization as pigmentation, they have significant therapeutically applications, such as improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 130 publications
1
32
0
Order By: Relevance
“…We used a catalase assay kit and DCFDA to measure the change of oxidative stress. The results showed that the fucoxanthin, which has a high antioxidant ability according to a previous study [12], increased the catalase activity (Figure 7D,E) and decreased the ROS level (Figure 7B,C,E,F), which may alter the 4-HNE-and high glucose-induced oxidative stress. This demonstrates the antioxidant effect to recover the oxidative stress caused by 4-HNE-and high glucose-induced retinopathy.…”
Section: The Antioxidant Ability Of Fucoxanthin In 4-hne-or High Glucose-induced Diabetes Retinopathysupporting
confidence: 66%
See 1 more Smart Citation
“…We used a catalase assay kit and DCFDA to measure the change of oxidative stress. The results showed that the fucoxanthin, which has a high antioxidant ability according to a previous study [12], increased the catalase activity (Figure 7D,E) and decreased the ROS level (Figure 7B,C,E,F), which may alter the 4-HNE-and high glucose-induced oxidative stress. This demonstrates the antioxidant effect to recover the oxidative stress caused by 4-HNE-and high glucose-induced retinopathy.…”
Section: The Antioxidant Ability Of Fucoxanthin In 4-hne-or High Glucose-induced Diabetes Retinopathysupporting
confidence: 66%
“…Fx has high antioxidative activity, greater than α-tocopherol [11]. In addition to being an antioxidant [12], Fx was found to lower the lipid peroxidation [13] and possess anti-fungal [14,15], anti-inflammatory [16], anti-hyperuricemia [17], and anti-tumor [18] effects. Fx was further researched regarding DNA damage and in having a protective effect on cardiovascular diseases [19].…”
Section: Introductionmentioning
confidence: 99%
“…Most carotenoids are tetraterpenoid compounds consisting of eight isoprene units and are responsible for the red, orange, and yellow colors of archaea and fungi, algae, plants. In the marine environment, these molecules are obtained by macroalgae, bacteria, and unicellular phytoplankton and play numerous and important functions, including protect chlorophyll via absorbing light energy and scavenging free radicals of oxygen [ 124 ]. Animals cannot synthesize carotenoids de novo and need to ingest carotenoids via supplementation or diet.…”
Section: Marine Drugs In Parkinson’s Diseasementioning
confidence: 99%
“…In addition, these CA obtained from algae can be co-extracted with other bioactive components such as polysaccharides or fatty acids. Therefore, the idea of incorporating CA in foods, nutraceuticals, or cosmetic products is of increasing interest due to their effective bioactive properties [ 173 ]. However, to develop and evaluate the viability of any food or cosmetic products that maintain these activities, it is necessary to know its bioactivity, bioavailability, and bioaccesibility [ 174 ].…”
Section: Mechanism Of Action Of Xanthophyllsmentioning
confidence: 99%